Performance Evaluation of Signalized Intersections Using MKJI 1997, PKJI 2023, and PTV VISSIM Software (Case Study: Jl. Perintis Kemerdekaan-Jl. Tritura-Jl. Sultan Hamid II-Jl. Ya"™ M. Sabran) - Putriningtiazti, Anissa; Azwansyah, Heri; Mayuni, Siti (Jurnal Teknik Sipil, 2024)
The intersection of Jl. Perintis Kemerdekaan - Jl. Tritura - Jl. Sultan Hamid II - Jl. Ya' M. Sabran is a signalized intersection that often occurs irregularities and long queues so it needs to be evaluated to determine the characteristics of the intersection, intersection performance in existing conditions, intersection performance in the next 5 and 10 years, and alternative treatments that can be done at the intersection. The performance evaluation of the signalized intersection was conducted using the 1997 Indonesian Road Capacity Manual (MKJI) method, the 2023 Indonesian Road Capacity Guidelines (PKJI), and traffic simulation using PTV VISSIM software. In the existing conditions of 2024, the recommended alternative 7 is geometric changes on the north (U), west (B), and east (T) arms accompanied by a ban on right turns on the north approach (U), resetting cycle times, and enforcing direct left turns on the north (U) and west (B) approaches.. In the 2029 projection conditions, the recommended alternative 10 is geometric changes on each arm accompanied by a ban on right turns on the north approach (U), setting cycle times, and enforcing direct left turns on the north (U) and west (B) approaches. In the 2034 projection conditions, the recommended alternative is alternative 14, which is a geometric change on each arm accompanied by a ban on right turns on the north approach (U), setting cycle times, and enforcing direct left turns on the north (U) and west (B) approaches.